Revealing Malay wisdom: traditional black ink production and its cultural significance - Abdul Razak, Rajabi; Mash'al, Nawal; Musa, Mukhtaruddin (Prince of Songkla University, Pattani Campus, 2023)
This study delves into the indigenous practices of Malays in crafting traditional black ink through the utilization of locally sourced natural resources. Traditionally, ink production has been intimately tied to the availability of natural materials within specific localities. In this pursuit, a specific black ink recipe, originating from the east coast of Peninsular Malaysia, takes centre stage in this exploration. The ink, designed as a water-based formulation, encapsulates three essential components: a colorant derived from soot and mangosteen charcoal, an adhesive harnessed from cashew gum exudate extracted from the bark of the cashew tree (Anacardium occidentale), and supplemental additives including black pepper, salt, and virgin coconut oil. The method used to reproduce the selected Malay traditional black ink, a simple OFAT (one-factor-at-a-time) method was adopted to screen the optimum composition of colouring agent, adhesive and additive. In order to simulate the historical context of early Malay manuscripts, the ink's compatibility with the European handmade paper was assessed, rendering it as the preferred substrate or writing medium. Further examination involving a panel of expert calligraphers who rigorously tested the formulated ink. In summation, this study contributes empirical validation to the enduring legacy of Malay traditional black ink, substantiating its quality, longevity, and permanence. The study underscores the intricate relationship between indigenous wisdom, cultural heritage, and the art of traditional ink production within the Malaysian context.